Advancements in automation, robotics and sensing : first International Conference, ICAARS 2016, Coimbatore, India, June 23-24, 2016, Revised selected papers /: first International Conference, ICAARS 2016, Coimbatore, India, June 23-24, 2016, Revised selected papers. (2016) - Unknown
No abstract available